Effect of intraoperative systemic magnesium sulphate on postoperative Richmond Agitation-Sedation Scale score after endovascular repair of aortic aneurysm under general anesthesia: A double-blind, randomized, controlled trial. - Haruna Kanamori; Yoshihito Fujita; Rina Joko; Ryota Ishihara; Yoshihiro Fujiwara (PLoS ONE, 2023)
Intraoperative magnesium has the effect of reducing postoperative opiate requirement, pain, and agitation. However, its effect on postoperative sedation and delirium is unclear. This study investigated the effect of magnesium on the postoperative Richmond Agitation-Sedation Scale (RASS) score and delirium following endovascular repair of aortic aneurysm (EVAR). Sixty-three consecutive patients diagnosed with abdominal (45) and thoracic (18) aortic aneurysm who underwent EVAR under general anesthesia were eligible. Patients were allocated randomly to the magnesium group (infusion of 30 mg•kg-1 magnesium in the first hour followed by 10 mg•kg-1 h-1 until the end of surgical procedure, targeting total 60 mg•kg-1) or the control group (0.9% saline at the same volume and rate). The primary outcome was whether magnesium had an effect on RASS score of patients at postoperative ICU admission. Secondary outcomes were effects on RASS score, numerical rating scale (NRS) score, Confusion Assessment Method for the Intensive Care Unit (CAM-ICU) until 24 h after postoperative ICU transfer, and length of ICU stay. At postoperative ICU admission, magnesium had no significant effect on the RASS score (0[-0.5 to 0] vs 0[0 to 0]; P = 0.114), but at 1 h the NRS score was statistically different, 2[0 to 4] vs 4[0 to 5] (P = 0.0406). However, other data (RASS score, NRS score, CAM-ICU and length of ICU stay) did not show a significant difference. Our results did not show that intraoperative magnesium of target total 60 mg•kg-1 affected postoperative RASS score for undergoing EVAR. Trial registration: The current study was registered according to WHO and ICMJE standards on 4 July 2018, under registration number the Japan Registry of Clinical Trials, iRCTs041190013.